ANALISIS KEPUTUSAN PEMBELIAN CHEESE TEA PADA TOKO KINI DI LIMO DEPOK - Kevin Ryan Fahrezy (2020)
The development of the beverage industry at this time can be chosen easily up Indonesia, this can be seen from the number of beverage shops that have been available everywhere. Can be seen ini sharing places such as malls and places frequented by other people used to start a beverage business. This research is a quantitative research on Cheese Tea products in Kini. The purpose of this study is to determine wheter the decision to purchase Cheese Tea in Kini is influenced by packaging, price, and sales promotion. The population in this study are users or who have shopped at Kini. Samples takes as many as 75 respondents, using non probability sampling technique and purposive sampling technique methods. Data collection was done through disturbing quetionnaires online to respondents. The analysis technique used is the PLS (Partial Least Square) analysis method using SmartPLS 3.0 software. The results of this study indicate that the variables of price and sales promotion have a significant effect on purchasing decisions. While the packaging variable has no influence and is not significant on purchasing decisions.